PERAN ORANG TUA DAN GURU DALAM MENINGKATKAN KEMAMPUAN CALISTUNG SISWA KELAS 1 (STUDI KASUS DI SEKOLAH DASAR ISLAM TERPADU TAHFIZH AL-MAKKI) - Adillah Herni; Salman; Radhiyatul Fithri; Yulia Septi Wahyuni (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
This study aims to determine the role of parents and teachers in improving reading, writing, and arithmetic (calistung) skills in first-grade elementary school students. Reading, writing, and arithmetic are essential basic skills for supporting children's learning success at subsequent levels of education. This study used a qualitative approach with a case study method. The research subjects consisted of parents, first-grade teachers, and students at a private elementary school. Data were collected through interviews, observation, and documentation. The results indicate that parental involvement in assisting children with learning at home, providing motivation, and creating a conducive learning environment significantly influences the development of children's reading, writing, and arithmetic skills. Meanwhile, the role of teachers in designing teaching strategies, using engaging learning media, and providing regular evaluations also contributes significantly to improving students' reading, writing, and arithmetic skills. Good collaboration between parents and teachers is key to optimally promoting students' academic development.